Investigation of In- Vitro Method of Antiulcer Activity - Kumar, Roshan (Journal for Research in Applied Sciences and Biotechnology, 2023)
It has long been known that medicinal plants include traditional therapeutic ingredients for the treatment and prevention of illnesses and disorders. In order to find out if hydroalcoholic extracts of fenugreek seeds may be used to treat ulcers, this study tested the extracts' capacity to neutralize acids and their ability to block H+/K+ - ATPase. A 1000 mg/ml concentration of the Seeds extract significantly reduced the acidity from 11.90 at the normal 500 mg/ml of Aluminium hydroxide + Magnesium hydroxide to 6.10. The maximum percentage of inhibition of the H+/K+ - ATPase was shown by petals extract at a concentration of 400 g/ml, which is less than the typical dose of esmoprazole (73.82%). The IC 50 value of extract of fenugreek seeds is shown to be 100 g/ml when compared to the average dose of esmoprazole, which is 82.5 g/ml. According to the findings of this study, fenugreek seeds contain compounds that have the ability to neutralize acids and block enzymes, making them a potential alternative treatment for digestive problems.